EFFECTIVE STRATEGIES IN QURAN MEMORIZATION AND REVISION (MURAJAAH) PRACTICES AMONG TAHFIZ STUDENTS IN MALAYSIA: A SYSTEMATIC REVIEW - Norafidah Md Yusup; Mohamad Marzuqi Abdul Rahim; Abd Hadi Borham (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This systematic literature review examines effective strategies for Quran memorization and revision (murajaah) among Tahfiz students in Malaysia. The issue addressed involves inconsistent retention outcomes and limited standardized pedagogical approaches, which may hinder students’ mastery of Quranic content. A rigorous search strategy was conducted using Scopus and ERIC, guided by the PRISMA framework, resulting in 26 relevant studies. Analysis of these publications was organized into three overarching themes: (1) Pedagogical Innovation, Teaching Methods, and Teacher Development in Islamic Education, (2) Curriculum Development, Policy, and Management in Islamic Education, and (3) Inclusivity, Special Needs, and Pandemic-Era Innovation in Islamic Education. Numerical findings across the included research indicate that integrated teacher training initiatives, structured curricular reforms, and adaptation to learners with diverse needs significantly enhance memorization accuracy. Risk, safety, and optimization models for decision support also emerged as possible frameworks, offering systematic methods to address resource constraints and promote secure learning environments. Results highlight that well-defined teacher development programs, supportive institutional policies, and technological innovations introduced during pandemic disruptions collectively contribute to improved murajaah practices. The review concludes with a recommendation for continued collaboration among educational authorities, school administrations, and community stakeholders to further strengthen implementation strategies. Emphasis is placed on comprehensive professional development, responsive curriculum design, and targeted inclusivity measures to ensure that Tahfiz students attain deeper engagement and stronger memorization outcomes in Quranic learning contexts.